Flaviviruses: Innate Immunity, Inflammasome Activation, Inflammatory Cell Death, and Cytokines - Pan, Yuhong; Cai, Wenjun; Cheng, Anchun; Wang, Mingshu; Yin, Zhongqiong; Jia, Renyong (Frontiers in Immunology, 2022)
The innate immune system is the host’s first line of defense against the invasion of pathogens including flavivirus. The programmed cell death controlled by genes plays an irreplaceable role in resisting pathogen invasion and preventing pathogen infection. However, the inflammatory cell death, which can trigger the overflow of a large number of pro-inflammatory cytokines and cell contents, will initiate a severe inflammatory response. In this review, we summarized the current understanding of the innate immune response, inflammatory cell death pathway and cytokine secretion regulation during Dengue virus, West Nile virus, Zika virus, Japanese encephalitis virus and other flavivirus infections. We also discussed the impact of these flavivirus and viral proteins on these biological processes. This not only provides a scientific basis for elucidating the pathogenesis of flavivirus, but also lays the foundation for the development of effective antiviral therapies.